3p+5q-6(3p-3q+3r)=

Simple and best practice solution for 3p+5q-6(3p-3q+3r)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3p+5q-6(3p-3q+3r)= equation:


Simplifying
3p + 5q + -6(3p + -3q + 3r) = 0
3p + 5q + (3p * -6 + -3q * -6 + 3r * -6) = 0
3p + 5q + (-18p + 18q + -18r) = 0

Reorder the terms:
3p + -18p + 5q + 18q + -18r = 0

Combine like terms: 3p + -18p = -15p
-15p + 5q + 18q + -18r = 0

Combine like terms: 5q + 18q = 23q
-15p + 23q + -18r = 0

Solving
-15p + 23q + -18r = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-23q' to each side of the equation.
-15p + 23q + -23q + -18r = 0 + -23q

Combine like terms: 23q + -23q = 0
-15p + 0 + -18r = 0 + -23q
-15p + -18r = 0 + -23q
Remove the zero:
-15p + -18r = -23q

Add '18r' to each side of the equation.
-15p + -18r + 18r = -23q + 18r

Combine like terms: -18r + 18r = 0
-15p + 0 = -23q + 18r
-15p = -23q + 18r

Divide each side by '-15'.
p = 1.533333333q + -1.2r

Simplifying
p = 1.533333333q + -1.2r

See similar equations:

| -4-8y=32 | | 0.35t^2-50t+1000=0 | | 0.05*t^2+54*t-500=0 | | 4(0)+10y=40 | | 4(0)+10y=42 | | 6p+5q-7(6p-3q+7r)= | | 7/8(p)=-16/4 | | x*2+8x-9=0 | | 4u+2v-2(4u-7v+3w)= | | x^2+4x^2-32x=0 | | 8/9-5m/9=14/9 | | x-6/7=23 | | 12=13/4x-10 | | 1/2-2/3x=5 | | 4-5(y+3)+6y=7 | | 2(3x-4)=3(2x+1)-11 | | 1/1/k | | 16v-81v^3= | | y=-3/2*2-3 | | y=-3/2*3-3 | | 49y^2+42y+9= | | y=-7/10(-7)+7 | | 1/3y-1/4y=1/y^2 | | 78.1%147= | | 2x-9=7x+4 | | 10x^2+6x-99=0 | | 10x^2+6x-99=100 | | 4y^2+3/2y-2=0 | | 7x^2-5=100 | | 235-5x=40x+20 | | 21p+52=10 | | 5/(2w+12)+1=-8/(w+6) |

Equations solver categories